Protein tyrosine phosphatase 69D is a substrate of protein O-mannosyltransferases 1-2 that is required for the wiring of sensory axons in Drosophila. - Monagas-Valentin, P.; Bridger, R.; Chandel, I.; Koff, M.; Novikov, B.; Schroeder, P.; Wells, L.; Panin, V. (Journal of Biological Chemistry, 2023)
Mutations in protein O-mannosyltransferases (POMTs) result in severe brain defects and congenital muscular dystrophies characterized by abnormal glycosylation of ?-dystroglycan (?-Dg). However, neurological phenotypes of POMT mutants are not well understood, and the functional substrates of POMTs other than ?-Dg remain unknown. Using a Drosophila model, here we reveal that Dg alone cannot account for the phenotypes of POMT mutants, and identify Protein tyrosine phosphatase 69D (PTP69D) as a gene interacting with POMTs in producing the abdomen rotation phenotype. Using RNAi-mediated knockdown, mutant alleles, and a dominant-negative form of PTP69D, we reveal that PTP69D is required for the wiring of larval sensory axons. We also found that PTP69D and POMT genes interact in this process, and that their interactions lead to complex synergistic or antagonistic effects on axon wiring phenotypes, depending on the mode of genetic manipulation. Using glycoproteomic approaches, we further characterized the glycosylation of the PTP69D transgenic construct expressed in genetic strains with different levels of POMT activity. We found that the PTP69D construct carries many O-linked mannose modifications when expressed in Drosophila with wild-type or ectopically upregulated expression of POMTs. These modifications were absent in POMT mutants, suggesting that PTP69D is a substrate of POMT-mediated O-mannosylation. Taken together, our results indicate that PTP69D is a novel functional substrate of POMTs that is required for axon connectivity. This mechanism of POMT-mediated regulation of receptor-type protein tyrosine phosphatase functions could potentially be conserved in mammals and may shed new light on the etiology of neurological defects in muscular dystrophies.